Persistência da desigualdade educacional no ensino fundamental - Baca, Mauricio Cabrera (2018)
The economic literature of the last decades points to education as an essential tool to foster economic growth and development and to reduce inequality and poverty. In this context, this study aims to evaluate the degree and persistence of educational inequality in Brazilian fundamental education, through the estimation of fixed-effect autoregressive models with bootstrap-based bias correction for dynamic panels by Everaert and Pozzi (2007). The results suggest that the persistence of inequality between the grades of the fifth year of primary school and the average of the grades and that of the ninth grade with their mean and with its best grades, are lower in the Southeast and South regions. However, there is no evidence of convergence process in these cases. In other words, in these comparisons, these differences between these school performances tend to tend to stay or grow rapidly in some regions and in the cities analyzed as a whole (Brazil). Especially when comparing the grades of the fifth year of primary school with its best grades. In this case, there is a high persistence of inequality in school performance and evidences of a strong process of divergence in the regions and in Brazil. Overall, such evidence indicates that these inequalities may persistor increase in the long run.